Pasien Spinocerebellar Ataxia 3 (SCA3) dengan neuropati perifer di Indonesia : laporan kasus - Iin Pusparini (Universitas Syiah Kuala, 2021)
Abstract Rationale: Spinocerebellar ataxia (SCA) 3, also known as Machado-Joseph Disease (MJD), is a neurodegenerative disease which involves cerebellum and its afferent and efferent pathways. Generally, the initial symptoms were gait disturbance, double vision, dysarthria, and vertigo.Patient concerns: a 43-year-old male, with known SCA3, presented hereditary ataxia had mild numbness in his both palms since two years ago. Sensory examination found no abnormality. Nerve Conduction Studies (NCS) showed severe axonal demyelinating sensorimotor peripheral neuropathy. In magnetic resonance imaging atrophy cerebellum with cerebral multiple lacunar infarction were seen. Diagnoses: SCA3 was diagnosed on the basis of clinical features, family pedigree, physical examination, electrophysiology study, neuroimaging, nerve biopsy, and genetic testing results. The electrophysiological manifestations revealed profound axonal demyelinating lesion in peripheral nerves. Genetic analysis was not done yet due to lack of availability of genetic testing in our country at this moment although it is the gold standard for diagnosis.Lessons: SCA3 with peripheral neuropathy represents a specific clinical entity that so far has never been described previously in Indonesia.Abbreviations: SCA3 = Spinocerebellar ataxia, MJD = Machado-Joseph Disease, NCS = Nerve Conduction Studies